Identification of the anisotropic elastic and damping properties of complex shape composite parts using an inverse method based on finite element model updating and 3D velocity fields measurements (FEMU-3DVF): Application to bio-based composite violin soundboards. (March 2018) - Viala, Romain; Placet, Vincent; Cogan, Scott
Abstract: Inverse methods have been used for decades to identify material properties, in parallel, or as a substitution for direct methods. Although it has proven a useful method for many types of materials and simple geometrical shapes, it has barely been used on complex shape parts. This is the main objective of the non-destructive method proposed in this study. The proposed inverse approach, based on both vibrational experiment data and Finite Element Model Updating (FEMU), is successfully applied to a violin soundboard made of flax-epoxy composite. Results show that, by minimizing the discrepancy between the experimental and numerical data, three rigidities and three loss factors can be determined simultaneously. The identified values of the constitutive elastic moduli and longitudinal loss factor are in agreement with those determined using quasi-static tests and dynamic mechanical analysis.